Anglicismos en el español peninsular - Czöndör, Klára (Verbum – Analecta Neolatina, 2001)
The author of this study analyses the influence of English on European Spanish. She claims that English has already affected almost all languages but the case is slightly different with respect to Spanish. She elucidates the difference through history of the contacts between the two languages. In the study we find a survey of the different levels of grammatical influence.